2004
DOI: 10.2183/pjab.80.349
|View full text |Cite
|
Sign up to set email alerts
|

Development of .BETA.-keto ester and malonate chemistry Palladium-catalyzed new reactions of their allylic esters

Abstract: Introduction.Palladium is now regarded as the most versatile metal among a number of transition metals used for organic synthesis.1) We started research on organopalladium chemistry in early 1960s, and discovered carbon-carbon bond formation by using palladium complexes for the first time. Since then we have carried out extensive studies on organopalladium. One topic of these studies is palladium-catalyzed reaction of allylic compounds via π-allylpalladium complexes. Among a number of new catalytic reactions d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Our working mechanism of the reaction is shown in Scheme . The reaction begins with absorption of a blue photon to give strongly oxidizing Ir­(III)* [Ir*­(III)/Ir­(II) = 1.21 V vs SCE in CH 3 CN], followed by reductive quenching by the amine , (NR 3 ≈ 0.50 V vs SCE). , This is supported by Stern–Volmer analysis ( 5a ). Next, the reduced Ir­(II) undergoes SET to collidinium salt 1h , (Ir­(II/III) = −1.37 V vs SCE; estimated E 1/2 = −1.27 V vs SCE in DMF), giving collidinium radical I and completing cycle A.…”
mentioning
confidence: 79%
“…Our working mechanism of the reaction is shown in Scheme . The reaction begins with absorption of a blue photon to give strongly oxidizing Ir­(III)* [Ir*­(III)/Ir­(II) = 1.21 V vs SCE in CH 3 CN], followed by reductive quenching by the amine , (NR 3 ≈ 0.50 V vs SCE). , This is supported by Stern–Volmer analysis ( 5a ). Next, the reduced Ir­(II) undergoes SET to collidinium salt 1h , (Ir­(II/III) = −1.37 V vs SCE; estimated E 1/2 = −1.27 V vs SCE in DMF), giving collidinium radical I and completing cycle A.…”
mentioning
confidence: 79%
“…Attempts to effect hydrolysis or dealkylation and decarboxylation of the methyl ester analogue of 21 into 3 were compromised by competitive β elimination of PMB‐OH. We solved this complication by use of the allyl ester 21 , which could be smoothly decarbalkoxylated with [Pd(PPh 3 ) 4 ] (HCO 2 H, Et 3 N) 36. The nonbasic conditions associated with this conversion of nitrile into methyl ketone render this strategy applicable to other base‐sensitive nitrile substrates.…”
Section: Methodsmentioning
confidence: 99%
“…4a,32 Specifically, it was found that [Cp*RuCl] 4 and bipyridine formed an effective catalyst for decarboxylative allylation (Scheme 8). The bipyridine (bpy) was found to be an essential ligand as it helped form the active monomeric catalyst from the tetrameric precatalyst.…”
Section: Decarboxylative Allylation Of Enolatesmentioning
confidence: 99%
“…In addition, studies of decarboxylative allylations have shown that there are several mechanisms for decarboxylative coupling that do not necessarily follow the simplified rubric shown in Scheme 1. While several accounts have been published on this topic in the last several years, 4 none has done so in the comprehensive manner of this review which covers relevant publications through August 2010.…”
Section: Introduction To Decarboxylative-couplingmentioning
confidence: 99%